(untitled) (St. Louis, Mo., 2013)
Introduction to Critical Care Nursing, 6th Edition offers clear, concise coverage of essential critical care concepts, technology, and procedures. Completely updated, evidence-based content addresses the latest advances in high-acuity care and emphasizes patient safety and optimum patient outcomes. Plus, an abundance of active learning resources and realistic case studies enables you to apply your knowledge and strengthen your critical thinking and clinical decision-making skills.
Keywords: Nursing care,Chăm sóc chỉ định,Chăm sóc điều dưỡng,Critical care